WhatsApp Self-Chat -Based Notes : A Strategy for Overcoming Boredom in Taking Notes on Islamic Religious Education Materials - Muhammad Ardhi Febriyan; Khairudin; Ferdiansyah (Lembaga Bale Literasi, 2025)
Study This aim overcome saturation take notes Islamic Religious Education material at SMKN 3 Kota Bima is dominated by resistance student to method conventional . Using design Classroom Action Research on 47 students , study This apply WhatsApp Note (Wa -Note) innovation based on self-chat as an intervention strategy. Data collection was carried out through observation , interviews , and scales analyzed saturation? in a way descriptive comparative using SPSS 27. Research results show significant effectiveness , average score saturation decrease sharp from 77.98 (very high category ) in the pre-cycle to 17.49 (very low ) at the end Cycle II with level high data homogeneity . In general qualitative , functional gadget succeed reconstructed from distraction become instrument reflection productive . Concluded that integration technology Wa -Note effective overcome saturation students and create ecosystem free learning? pressure